Inovasi Media Pembelajaran Digital melalui E-Book Biologi (EBoBi) Berbasis Etnosains Untuk Membangun Higher Order Thinking Skills Siswa - Nukhbatul Bidayati Haka; Icha Dwi Tiara; Meita Dwi Solviana (Lembaga Bale Literasi, 2026)
Higher-order thinking skills (HOTS) are crucial for 21st-century students to face global challenges and solve complex problems. However, high school biology learning is still dominated by lectures and conventional textbooks. Students often memorize concepts without understanding their applications, while local wisdom such as the Pangan Balak Lampung tradition has not been utilized as a learning resource. The use of interactive ethnoscience-based e-books has the potential to connect scientific concepts with local culture and enhance learning motivation. This study aimed to develop an ethnoscience-based Biology E-Book (EBOBI) on the digestive system topic for Grade XI students using the 4D R&D model (Define, Design, Develop, Disseminate). The research subjects included material, media, and language validators, biology teachers, and students from SMA Negeri 1 Punduh Pidada and SMA Negeri 2 Padang Cermin. Data were collected through validation sheets, teacher and student response questionnaires, and HOTS tests. Validation results showed excellent feasibility (material experts 90.3%, media experts 92.1%, and language experts 89.7%). Limited trials achieved a practicality score of 91.2%, while broader trials reached 93.5%, accompanied by positive responses from teachers and students. The average HOTS score of students was 82.4% (high category). Thus, the ethnoscience-based EBOBI is considered valid, practical, and effective as an innovative learning medium to improve students’ HOTS.